CPT1A through succinylation regulates the CTCF/LINC01503‒91aa feedback loop to promote gemcitabine resistance in pancreatic ductal adenocarcinoma - De‐Liang Fang; Si‐Yuan Lu; Zhi‐De Liu; Qiong‐Cong Xu; Yang‐Yinhui Yu; Ying‐Qin Zhu; Ming‐Jian Ma; Jing‐Yuan Ye; Xiao‐Yu Yin (Clinical and Translational Medicine, 2026)
Abstract Background Pancreatic ductal adenocarcinoma (PDAC) is one of the most malignant solid tumors, characterized by strong invasiveness and poor clinical prognosis. Recent studies have revealed that long non‐coding RNAs (lncRNAs) can serve as translational templates to produce functional microproteins, which further participate in the regulation of cellular metabolism. Objective To investigate the function and detailed mechanism of the novel protein 1503–91aa encoded by LINC01503 in gemcitabine‐resistant PDAC, and explore the possibility of clinical translation. Methods The differentially expressed lncRNAs in gemcitabine‐resistant PDAC cells with coding potential were screened by whole transcriptome sequencing and coding prediction from database. A series of cellular, molecular and in vivo assays were performed to characterize the novel microprotein 1503–91aa, its upstream transcriptional regulation, and its role in mediating PDAC gemcitabine resistance. A series of molecular assays clarified the interaction between 1503–91aa and carnitine palmitoyl transferase 1A (CPT1A). Finally, the clinical translational potential of the CPT1A inhibitor etomoxir in combination with gemcitabine was validated using our center's gemcitabine‐resistant patient‐derived xenograft (PDX) model. Results Here, we revealed that LINC01503 had coding potential in drug‐resistant PDAC and encoded a novel 91–amino acid protein, which designated as 1503–91aa. Simultaneously, LINC01503's transcriptional regulation is mediated by CTCF and then 1503–91aa expression levels were significantly upregulated in PDAC. Functionally, 1503–91aa, instead of LINC01503 confers gemcitabine resistance in vitro and in vivo. Mechanistically, 1503–91aa targeted the CPT1A, and up‐regulated CPT1A activity through antagonizing the association of malonyl‐CoA (MCoA), the best known metabolic intermediate inhibiting CPT1A, to promote fatty acid oxidation (FAO) and thereby facilitate gemcitabine resistance. We discovered that CPT1A functions as a succinyltransferase to regulate the succinylation level of CTCF, thereby controlling its stability. This establishes a positive feedback loop that continuously sustains 1503–91aa protein levels to regulate CPT1A activity. Consequently, this induces persistent FAO in PDAC cells, ensuring a continuous energy source that facilitates gemcitabine resistance in pancreatic cancer. Notably, the combined application of the etomoxir and gemcitabine exerts a synergistic effect on PDAC. Conclusions These findings provide novel insights into the molecular mechanisms underlying gemcitabine resistance in PDAC and highlight CTCF/LINC01503–91aa/CPT1A feedback loop as a potential prognostic biomarkers and therapeutic targets. Key points We identified that LINC01503 is capable of encoding the protein product 1503–91aa. 1503–91aa competed with MCoA to unleash CPT1A activity for fatty acid oxidation and thereby mediating gemcitabine resistance in PDAC. Etomoxir and gemcitabine have synergistic effects in gemcitabine efficiency.